Autosomal dominant frontometaphyseal dysplasia: Delineation of the clinical phenotype. Issue 7 (12th May 2017) - Wade, Emma M.; Jenkins, Zandra A.; Daniel, Philip B.; Morgan, Tim; Addor, Marie C.; Adés, Lesley C.; Bertola, Debora; Bohring, Axel; Carter, Erin; Cho, Tae‐Joon; de Geus, Christa M.; Duba, Hans‐Christoph; et al.
Abstract : Frontometaphyseal dysplasia (FMD) is caused by gain‐of‐function mutations in the X‐linked gene FLNA in approximately 50% of patients. Recently we characterized an autosomal dominant form of FMD (AD‐FMD) caused by mutations in MAP3K7, which accounts for the condition in the majority of patients who lack a FLNA mutation. We previously also described a patient with a de novo variant in TAB2, which we hypothesized was causative of another form of AD‐FMD. In this study, a cohort of 20 individuals with AD‐FMD is clinically evaluated. This cohort consists of 15 individuals with the recently described, recurrent mutation (c.1454C>T) in MAP3K7, as well as three individuals with missense mutations that result in substitutions in the N‐terminal kinase domain of TGFβ‐activated kinase 1 (TAK1), encoded by MAP3K7 . Additionally, two individuals have missense variants in the gene TAB2, which encodes a protein with a close functional relationship to TAK1, TAK1‐associated binding protein 2 (TAB2). Although the X‐linked and autosomal dominant forms of FMD are very similar, there are distinctions to be made between the two conditions. Individuals with AD‐FMD have characteristic facial features, and are more likely to be deaf, have scoliosis and cervical fusions, and have a cleft palate. Furthermore, there are features only found in AD‐FMD in our review of the literature including valgus deformity of the feet and predisposition to keloid scarring. Finally, intellectual disability is present in a small number of subjects with AD‐FMD but has not been described in association with X‐linked FMD.